Cardiovascular Complications of HIV-Associated Immune Dysfunction - Akram M. Zaaqoq; Faisal A. Khasawneh; Roger D. Smalligan (Cardiology Research and Practice)
Prolonged survival in HIV infection is accompanied by an increased frequency of non-HIV-related comorbidities. It is suggested that cardiovascular diseases (CVD) occur earlier among HIV-positive patients compared with HIV-negative patients, and at a higher rate. Several factors have been proposed which can be categorized into traditional and nontraditional risk factors. Immune dysfunction is a nontraditional risk factor that contributes significantly to cardiovascular pathology. Markers of inflammation are elevated in HIV-infected patients, and elevations in markers such as high-sensitivity C-reactive protein, D-dimer, and interleukin-6 (IL-6) have been associated with increased risk for cardiovascular disease. However, the data currently suggest the most practical advice is to start antiretroviral therapy early and to manage traditional risk factors for CVD aggressively. A better understanding of the mechanisms of CVD in this population and further efforts to modify chronic inflammation remain an important research area.